Minorities or Nations? Discourses and Policies of Recognition of Indigenous Peoples’ Rights (Alternautas, 2014)
The definition of Indigenous peoples as either “minorities” or as “nations” has a profound impact on public policies. Indigenous people are seen as ethnic minorities and, despite enjoying special juridical protection, they cannot expect to be treated in a different way, for example as the Right to Previous Consultation suggests. In summary, the perspectives presented here put forward the idea that if special rights are granted to Indigenous peoples it is to integrate them into Peruvian society - not to grant them different treatment, which would affect the formal equality that the law grants to every citizen. These discourses stem from understanding Indigenous rights as ethnic minority rights, to ensure their inclusion within the political and economic framework of the state, 'tolerating' their cultural diversity. The problem with the above comments is the understanding of Indigenous peoples as minorities and not as peoples.